THE TOTAL IRREGULARITY STRENGTH OF SOME COMPLETE BIPARTITE GRAPHS - Pranaya D. M. Taihuttu; Meilin I. Tilukay; F. Y. Rumlawang; Z. A. Leleury (Pattimura Proceeding, 2017)
This paper deals with the total irregularity strength of complete bipartite graph where and .